The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0037-86822010000300015
|View full text |Cite
|
Sign up to set email alerts
|

Características epidemiológicas e clínicas das reações hansênicas em indivíduos paucibacilares e multibacilares, atendidos em dois centros de referência para hanseníase, na Cidade de Recife, Estado de Pernambuco

Abstract: RESUMOIntrodução: As reações são frequentes e importantes no contexto da hanseníase, representando uma significativa parcela de pacientes com incapacidades e submetidos ao retratamento da hanseníase. A caracterização clínico-epidemiológica dos padrões reacionais é primordial para o manejo dos pacientes. O objetivo desse trabalho é descrever as características epidemiológicas e clínicas das reações hansênicas em indivíduos paucibacilares e multibacilares. Métodos: Estudo transversal onde foram avaliados 201 pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
1
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 12 publications
10
41
1
18
Order By: Relevance
“…It is known that the closer to the lepromatous pole, the greater the likelihood of developing disabilities 19 . The development of leprosy reaction type 1 or reverse reaction was observed in a majority of patients in this study, similar to results reported by Teixeira et al 17 . Reactional states are the leading cause of nerve damage and physical disability caused by leprosy; therefore, monitoring and treating leprosy reactions is essential 20 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is known that the closer to the lepromatous pole, the greater the likelihood of developing disabilities 19 . The development of leprosy reaction type 1 or reverse reaction was observed in a majority of patients in this study, similar to results reported by Teixeira et al 17 . Reactional states are the leading cause of nerve damage and physical disability caused by leprosy; therefore, monitoring and treating leprosy reactions is essential 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were found in Teixeira et al 17 . The predominance of multibacillary forms is due, among many factors, to delayed diagnosis, which affects maintenance of the epidemiological chain and can serve as a source of increased transmission 14,17 . The borderline clinical form was the most prevalent form of leprosy in this study, corroborating the results of Alves et al 18 .…”
Section: Discussionsupporting
confidence: 92%
“…Research studies have indicated the males predominate in new cases and in relapsed cases of leprosy; men are between 0.21 and 0.81 times more likely to have a relapse when compared to women. This may be related to the persistent behavior of low search for health services in the case of men [12,13,14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…1 Os poucos estudos sobre mortalidade por hanseníase realizados em São Paulo mostram a mesma predominância de óbitos em pessoas do sexo masculino. [14][15][16] Sabe-se que os homens são mais frequentemente acometidos 8,17,18 e mais propensos ao desenvolvimento de formas mais graves da doença. 8 Em relação aos aspectos sociais dos indivíduos que morreram por hanseníase como causa básica, cerca de 60% possuíam baixo nível de escolaridade, achado semelhante ao de um estudo dos óbitos por hanseníase ocorridos no Brasil no mesmo período.…”
Section: Discussionunclassified
“…6 Porém, indivíduos curados pela poliquimioterapia para hanseníase (PQT) e, portanto, curados segundo o Sinan, podem apresentar condições clínicas que incluem estados reacionais, incapacidades físicas e sequelas decorrentes da doença. 7,8 Tais condições não são registradas na Declaração de Óbito (DO).…”
Section: Introductionunclassified